Update of the erosive rain factor in Slovakia using data from the period 1961–2009 - ONDERKA, Milan; PECHO, Jozef (Contributions to Geophysics and Geodesy, 2019)
An update of the rainfall erosivity factor (R-factor) estimated for 95 locations throughout the entire territory of Slovakia is presented in this paper. We analyzed rainfall time series with 1-minute resolution provided by the Slovak Hydrometeorological Institute. The data cover the period 1961–2009. The rain gauges are located at altitudes ranging from 97m a.s.l. up to 1322m a.s.l. and cover the broadest possible range of geographic regions and climatic conditions in Slovakia with reliable rainfall measurements. First, rainfall episodes were isolated by applying the fundamental rule that two subsequent rains are separated by at least six hours of no rainfall. A total of 116,710 rainfall events were identified and analyzed. A rainfall event was classified as erosive if the two following criteria were satisfied: the maximum 15-minute intensity 6.25mm (i.e. 25mmhr−1, as originally used in the U.S.L.E. model, and/or rainfall depth was greater than 12.5 mm. The presented estimates of R-factor are based on 18,467 identified erosive rainfall events. Furthermore, the minimum length of rainfall record necessary for reliable estimates of Rfactor has been estimated by spectral analysis. The Lomb-Scargle periodogram identified periodic behavior of the total kinetic rainfall energy and rainfall 15-minute intensities. We suggest that these periodicities are attributable mainly to the 11-year Sun spot cycle, the 18.6-year Luni-Solar cycle, and their higher harmonics. The spectral analysis also revealed that in order to capture the temporal variability the minimum length of timeseries in calculating R-factors is 14–15 years. We estimate that the long-term mean annual R-factor in Slovakia ranges from 34.8MJ ha−1 cm hr−1 (at Gabčíkovo station) to 138MJha−1 cm hr−1 (at Tatranská Javorina station). The median value of the mean annual R-factors for the whole country is 71.13 MJha−1 cm hr−1.